3 - Between the Clinic and the Community: Temporality and Patterns of ART Adherence in the Western Cape Province, South Africa1 - Larkan Fiona; van Wyk B; Stevens P; Saris A.J. (African Sociological Review, 2015)
In an ethnographic study conducted over thirty months in South Africa’s Western Cape Province ending in 2012, we explored ART adherence amongst almost 200 patients attending three clinics. This setting contained significant political, structural, economic and socio-cultural barriers to the uptake of, and adherence to, treatment. Such barriers certainly impacted patient drug use and the labelling of clients as ‘adherent’ or ‘non-adherent’. Yet, as our fieldwork developed, it became apparent that these labels also bore little relationship to the amount and regularity of drug consumption outside the clinic. Indeed, the people that we knew moved through these labels in ways that could not simply be explained by brute socio-economic circumstances, poor understanding of the functions of the drugs, or varying levels of family and community support, which themselves often changed over time. This paper presents four on-going ‘patterns of adherence’, which are clearly discernible in the communities in which we worked. Each pattern is demonstrated through the life of an ‘index patient’ whose case is seen to be representative of the range of experiences and practices observed under the terms ‘adherent’ and ‘non-adherent’. We argue that such terms are deeply contextual and, crucially, temporally situated. The complex intertwining of political, economic, socio-cultural, gender, and biological factors that constitute the lives of participants exists in time and we call for a focus on evolving lives in relationship to changing health systems that can follow (and respond to) such developments to better deliver both information and services.